Comments on “Vision-based finite-time uncooperative target tracking for UAV subject to actuator saturation” [Automatica 130 (2021) 109708] - Su, Yuxin (Automatica (Oxford), 2024)
This correspondence points out two fatal flaws in Sun, Zhu, Zuo, and Basin (2021), making the proposed approach untenable.